2015
DOI: 10.4236/msce.2015.312013
|View full text |Cite
|
Sign up to set email alerts
|

First Principles DFT Study of Hydrogen Storage on Graphene with La Decoration

Abstract: The properties of hydrogen storage on graphene with La decoration are investigated using a firstprinciples plane-wave pseudopotential method based on the density functional theory in this paper. The clustering problem of La decorated graphene is considered and B doping can solve it effectively in theory. We obtain the stable geometrical configuration of the modified system and the properties of hydrogen storage are excellent. It can absorb up to 6 H 2 molecules with an average adsorption energy range of −0.529… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We considered the model [23] and further quantum chemical calculations were applied by using density functional theory. We applied Vienna ab initio simulation code (VASP) [24][25] within PAW method.The exchange and correlation within local density approximation have been selected for our studied system.…”
Section: Methodsmentioning
confidence: 99%
“…We considered the model [23] and further quantum chemical calculations were applied by using density functional theory. We applied Vienna ab initio simulation code (VASP) [24][25] within PAW method.The exchange and correlation within local density approximation have been selected for our studied system.…”
Section: Methodsmentioning
confidence: 99%
“…So far, different doped-decorated graphene systems have been studied for hydrogen storage with promising results [ 54 , 55 , 60 , 91 , 93 , 107 , 126 , 128 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ]. In this approach, the doping atoms are embedded in the graphene structure, while the decorating atoms are deposited on the doped graphene sheet.…”
Section: Hydrogen Storage On Doped-decorated Graphenementioning
confidence: 99%
“…Up to nine H 2 molecules could be adsorbed on Ni- and Ti-decorated B-doped graphene with an adsorption energy of −0.43 and −0.41 eV/H 2 , respectively. Another study examined the use of La-decorated B-doped graphene for hydrogen storage by using the LDA method [ 142 ] and showed that up to six H 2 molecules were adsorbed with an adsorption energy of −0.53 eV/H 2 . These studies show that decorated-doped graphene systems are good candidates for hydrogen storage.…”
Section: Hydrogen Storage On Doped-decorated Graphenementioning
confidence: 99%
“…Therefore, it is a very interesting material candidate for hydrogen storage. [8][9][10][11][12][13][14] In all of these materials, such as 2D graphene, the Si 2 BN monolayer has garnered a lot of attention for its potential use and application of hydrogen storage. [1][2][3][4] After taking inspiration from the above work, we have performed a detailed study on the structure, electronic, and optical properties of functionalized graphenelike solid Si 2 BN QD.…”
Section: Introductionmentioning
confidence: 99%